2016
DOI: 10.1038/pr.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

ERP evidence of preserved early memory function in term infants with neonatal encephalopathy following therapeutic hypothermia

Abstract: Infants with NE have preserved recognition memory function after TH. The spatially different recognition memory processing after early brain injury may represent compensatory changes in the brain circuitry and reflect a benefit of TH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We analyzed mean data from adjacent groupings of electrodes ( Figure 1 ) where we noted the most activity to stimuli, in the frontal, central, and posterior (slow wave only) scalp regions. These areas are consistent with the most prominent areas of activity in other studies of newborn auditory recognition memory ( 18 20 , 22 ).…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…We analyzed mean data from adjacent groupings of electrodes ( Figure 1 ) where we noted the most activity to stimuli, in the frontal, central, and posterior (slow wave only) scalp regions. These areas are consistent with the most prominent areas of activity in other studies of newborn auditory recognition memory ( 18 20 , 22 ).…”
Section: Methodssupporting
confidence: 90%
“…Both study group and control infants underwent auditory recognition memory assessment via ERP at the University of Minnesota Center for Neurobehavioral Development, as previously described ( 20 ). Infants were targeted for testing at 44 weeks post-conceptual age (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the advent of TH, studies have shown that children with a history of HIE had poorer working memory, long-term episodic memory, and verbal and visual memory [ 9 , 10 , 11 ]. While some studies have shown continued memory dysfunctions in children with history of HIE even after TH [ 3 , 12 ], our group showed that newborns with HIE who received TH had preservation of recognition memory function at an electrophysiologic level, yet an alteration in the brain circuitry underlying that function at 2 weeks of age [ 13 ].…”
Section: Introductionmentioning
confidence: 92%